The Ethics in Literature
XI, 281 p.
Keywords: The question of ethics has dominated recent developments within the humanities. This volume brings together the most recent theories of ethics and reading and applies them to a wide variety of literary texts. Ethical and literary issues explored by the contributors include biography, sensibility, national identity, feminism, postcolonialism, religion, subjectivity and stylistics. Literary authors and philosophers/theorists discussed range from Shakespeare and Mary Shelley to Michele Roberts and Salman Rushdie, and from Kant and Coleridge to Derrida and Levinas.